Holistic Model for SMEs Growth Studies: A Conceptual Overview - Runtuk, Johan K.; Wirjodirdjo, Budisantoso; Vanany, Iwan (Institut Teknologi Sepuluh Nopember, 2014)
There have been extensive studies on firm’s growth. The determinants of growth are widely discussed among scholars. However, previous studies in context of small and medium enterprises (SMEs) growth are still limited and tend to focus on specific factor that affect firm’s growth. This approach can specifically measure the direct contribution of the factor to the growth, but it has been criticized due to its limited perspective and applicability. In this study, we investigate related studies on firm’s growth, specifically on SMEs growth, and proposing a holistic model to get a thorough understanding about the success or the failure of SMEs to grow. Based on a thorough review of the extant literature, we have identified several main theories/concepts on firm’s growth studies. Finally, we offer a conceptual overview for SMEs growth studies.